PEMETAAN SEKTOR EKONOMI UNGGULAN DAERAH DALAM RANGKA PEMASARAN PELUANG INVESTASI DI KABUPATEN INDRAGIRI HULU PROVINSI RIAU - afred suci; satria tri nanda (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: Opening investment opportunity, either domestic or overseas, becomes one of strategy to empowering whole local assets and resources available. Investment needs to be carefully planned according to its local potention so that it can be focusly implemented to create a high competitive power. This study aims to identify the potential economy sector to invest on economic leading sector in Indragiri Hulu regency. Research datas are secondary that consist of Gross Domestic Product, economic growth and sectoral economic contribution, and then processed and interpreted by using Location Quotion, Shift Share Analysis and Klassen Typology. Study reveals that all sectors in Indragiri Hulu regency have chance to be the target of investment marketing strategy. Eventhough, not all of them are leading sectors, deficit sectors, however, also have chance to be the potential investment target to supply the unmet local and regional needs. Leading economic sectors are agriculture; water supply, garbage, waste and recycling management; construction; trade and retail; transportation and warehousing; accomodation and culinary; real estate/property; education; health and social activity, and; other services.Keywords: Leading Local Economic Sector Investment